2012
DOI: 10.1080/08327823.2012.11689824
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microwave Treatment on Animal Fodder

Abstract: Preliminary research has suggested that in vitro dry matter disappearance (DMD) of some poor quality animal fodder materials can be improved by microwave treatment. Laboratory scale experiments revealed that dry matter percentage of Lucerne hay increased by 1.7% as microwave treatment time increased from 0 to 80 seconds. The in vitro DMD of lucerne hay increased by 14.9% during the same microwave treatment. In addition it was also demonstrated that microwave treatment significantly increased starch digestion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…Lucerne hay showed the highest increase of all hays in the present study, with increases in in DMD content (11%) and DOMD content (14%) at 60 s MW treatment compared with the control. The level of increase in the DMD content of lucerne hay was similar to the finding of Brodie et al (2012) [13]. The study showed that DMD increased by 14.9% when treated for 80 s MW treatment (750 W) compared with the control.…”
Section: Dry Matter Digestibility and Digestibility Of Organic Matter In Dry Mattersupporting
confidence: 82%
See 2 more Smart Citations
“…Lucerne hay showed the highest increase of all hays in the present study, with increases in in DMD content (11%) and DOMD content (14%) at 60 s MW treatment compared with the control. The level of increase in the DMD content of lucerne hay was similar to the finding of Brodie et al (2012) [13]. The study showed that DMD increased by 14.9% when treated for 80 s MW treatment (750 W) compared with the control.…”
Section: Dry Matter Digestibility and Digestibility Of Organic Matter In Dry Mattersupporting
confidence: 82%
“…One possible reason could be due to the increase of detection of unavailable cell wall-bound CP during the determination of CP [21], which might become available for detection due to cell wall destruction in this study (Figures 1 and 2). Further, other feed studies suggested that exogenous protein factors (structure, content of antinutritional factor, starch and non-starch polysaccharides) and endogenous factors (cross-linkage, molecular structure, hydrophobicity) [22] could be altered by heat treatment [23], which could in turn impact on protein availability and utilization in animals [13]. Future work is needed to better understand how and why CP content change in response to MW treatment.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on changes in water exposed to microwaves include a change in pH and water molecules (Wong et al, 2009). In a survey of (Brodie et al, 2012) on the use of microwave in the Lucerne treatment. The total content and loss of dry matter and ratios of complete protein were measured in digest residue compared to untreated sam- Different letters in each column mean signi icant differences at P>0.05 level ples during cellulose digestion in laboratory pepsin.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this effect, the continuous rotation of polarized molecules causes the conversion of electromagnetic energy to heat [2]. Other examples of such applications are wood drying [3][4], microwav e treatment of animal fodder [5], disinfection of walnuts [6], wheat and stored product pest control [7] thermal disinfection of soils [8], anti-freezing [9], and weed control in farms [1].…”
Section: Introduction1mentioning
confidence: 99%